QIRA`AT SAB’AH DALAM MEMBACA AL-QUR`AN: (Tinjauan Sejarah Diturunkannya Al-Qur`an) - Ahmad Zubairin (Jurnal Asy-Syukriyyah, 2022)
The discrepancies qiraat the Koran is not a fictitious result of the creation or the scholars qiraat experts. Various qira'at Qur'an is solely delivered by history with a saheeh sanad from the Prophet. Differences qira'at kaifiyat originated from a teacher in delivering / qira'at read it to his disciples, and this activity continues from one generation to the next. From some differences'i'rab proposed by scholars of language and words or phrases mufassirin the verses of the Koran, was only partially affect the difference of meaning.